An Abrupt and Brutal Audit: An Analysis of the Crisis Management Response of UK Museums and Heritage Attractions to the Covid-19 Pandemic. Issue 3 (3rd July 2021) - Mackay, Rachel
Abstract: In March 2020, museums and heritage sites faced indefinite closure as the United Kingdom government sought to curb the spread of a new virus. Covid-19 brought a new kind of crisis to the heritage sector, but it also brought a learning opportunity. This article outlines a research project, conducted at the height of the pandemic, which sought to assess the museum and heritage sector crisis management response to Covid-19. In the summer of 2020, ten interviews were conducted with managers working in UK museum and heritage sites. In addition, contemporary literature relating to the impact of Covid-19 on the sector was reviewed. Three key themes were identified and explored: Experience and planning; Impact on staff; Coordination and collaboration The study highlighted a range of lessons learned. Firstly, it showed that in the main, the sector was not prepared to deal with a pandemic of this nature. Secondly, it showed that the emotional impact on staff was profound; but also that there were increased efforts to support wellbeing. Thirdly, the research showed that there was a lack of clear information from official channels, and that this impacted decisionmaking at a site level. However, it has also revealed evidence that in the absence of official guidance, sector collaboration was significant and viewed by participants as a key positive outcome of the crisis. The article concludes with recommendations to improve crisis management in the future and offers practical resources as a starting point for greater sector preparedness.